THREE-DIMENSIONAL ASPECTS OF THE MAIN CHARACTER IN DELIA OWENS' WHERE THE CRAWDADS SING - Wahyuni Khotimah; Bunyamin Faisal Syarifudin; Agry Pramita (Universitas Islam Negeri Sunan Gunung Djati, 2023)
Egri's three-dimensional theory (1923) was employed to examine the multifaceted aspects of Catherine Danielle Clark, the main character in Delia Owens' novel